Ecology-Based Integrated Pest Management Strategies to Enhance Sustainable Agricultural Productivity - Parwito, Parwito; Hendri Bustamam (Jurnal Agricultural Science, 2025)
Excessive reliance on synthetic pesticides in modern agricultural systems has caused various serious problems, including pest resistance, ecosystem damage, and threats to human health. Ecology-based Integrated Pest Management (IPM) emerges as a promising alternative approach to address these challenges while enhancing agricultural productivity sustainably. This research aims to analyze ecology-based IPM strategies and evaluate their effectiveness in improving sustainable agricultural productivity. The research method uses a qualitative approach with systematic literature review of scientific publications from 2019 to 2024, case studies of IPM implementation in various countries, and comparative analysis between IPM systems and conventional pest management. Data were collected from 78 reputable journal articles, technical reports from international agricultural organizations, and field practice documentation. The analysis results show that ecology-based IPM implementation can reduce synthetic pesticide use by up to 65 percent while maintaining or even increasing crop productivity by 12 to 18 percent compared to conventional systems. Key components of IPM strategy include systematic pest population monitoring, utilization of natural enemies through conservation and augmentation, crop diversification and rotation to disrupt pest life cycles, use of pest-resistant varieties, habitat manipulation to enhance functional biodiversity, and application of biological and selective pesticides only when necessary based on economic thresholds. IPM implementation faces challenges including higher technical knowledge requirements, time investment for intensive monitoring, and transition periods requiring ecosystem adjustment. However, long-term benefits including ecological sustainability, better soil health, reduced input costs, and agricultural system resilience to climate change make IPM a highly prospective strategy. Policy recommendations include development of farmer training programs, incentives for IPM practice adoption, support for research and development of pest-resistant varieties, and integration of IPM in agricultural education curricula.